Effects of Anti-CD20 Antibody Therapy on Immune Cell Dynamics in Relapsing-Remitting Multiple Sclerosis - Willison, Alice G; Hagler, Ramona; Weise, Margit; Elben, Saskia; Huntemann, Niklas; Masanneck, Lars; Pfeuffer, Steffen; Lichtenberg, Stefanie; Golombeck, Kristin S; Preuth, Lara-Maria; Rolfes, Leoni; Öztürk, Menekse; et al. (Cells, 2025)
INTRODUCTION: The efficacy of anti-CD20 antibodies has significantly contributed to advancing our understanding of disease pathogenesis and improved treatment outcomes in relapsing-remitting multiple sclerosis (RRMS). A comprehensive analysis of the peripheral immune cell profile, combined with prospective clinical characterization, of RRMS patients treated with ocrelizumab (OCR) or ofatumumab (OFA) was performed to further understand immune reconstitution following B-cell depletion. METHODS: REBELLION-MS is a longitudinal analysis of RRMS patients treated with either OCR (n = 34) or OFA (n = 25). Analysis of B, T, natural killer (NK) and natural killer T (NKT) cells at baseline, month 1, and 12 was performed by multidimensional flow cytometry. Data were analyzed by conventional gating and unsupervised computational approaches. In parallel, different clinical parameters were longitudinally assessed. Twenty treatment-naïve age/sex-matched RRMS patients were included as the control cohort. RESULTS: B-cell depletion by OCR and OFA resulted in significant reductions in CD20+ T and B cells as well as B-cell subsets, alongside an expansion of CD5+CD19+CD20- B cells, while also elevating exhaustion markers (CTLA-4, PD-1, TIGIT, TIM-3) across T, B, NK, and NKT cells. Additionally, regulatory T-cell (TREG) numbers increased, especially in OCR-treated patients, and reductions in double-negative (CD3+CD4-CD8-) T cells (DN T cells) were observed, with these DN T cells having higher CD20 expression compared to CD4 or CD8 positive T cells. These immune profile changes correlated with clinical parameters, suggesting pathophysiological relevance in RRMS. CONCLUSIONS: Our interim data add weight to the argumentation that the exhaustion/activation markers, notably TIGIT, may be relevant to the pathogenesis of MS. In addition, we identify a potentially interesting increase in the expression of CD5+ on B cells. Finally, we identified a population of double-negative T cells (KLRG1+HLADR+, in particular) that is associated with MS activity and decreased with CD20 depletion.
Keywords: Multiple Sclerosis, Relapsing-Remitting; immune reconstitution; longitudinální studie; Killer Cells, Natural; lidé; Middle Aged; mužské pohlaví; ocrelizumab; Adult; autoimmunity; B-lymfocyty; ženské pohlaví; Humans; B-Lymphocytes; Antibodies, Monoclonal, Humanized; ofatumumab; Antigens, CD20; lidé středního věku; relabující-remitující roztroušená skleróza; Longitudinal Studies; dospělí; buňky NK; antigeny CD20; Female; humanizované monoklonální protilátky; Male; multiple sclerosis